Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41467-020-17146-z
|View full text |Cite
|
Sign up to set email alerts
|

E2F-dependent transcription determines replication capacity and S phase length

Abstract: DNA replication timing is tightly regulated during S-phase. S-phase length is determined by DNA synthesis rate, which depends on the number of active replication forks and their velocity. Here, we show that E2F-dependent transcription, through E2F6, determines the replication capacity of a cell, defined as the maximal amount of DNA a cell can synthesise per unit time during S-phase. Increasing or decreasing E2F-dependent transcription during S-phase increases or decreases replication capacity, and thereby repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 51 publications
(66 reference statements)
3
21
0
Order By: Relevance
“…The authors report an increased speed of DNA replication but an unaltered number of active origins. The increase in DNA replication speed resulted in the formation of DSBs which triggered a DNA damage response in the second cell cycle after E2F6 siRNA, suggesting a different mechanism than the one reported for DNA replication stress ensuing from cyclin E overexpression (Pennycook et al, 2020 ). Interestingly, loss of E2F1 and E2F2 in mice resulted in DNA damage (Iglesias-Ara et al, 2015 ).…”
Section: E2f1 Dysregulation As a Cause Of Dna Replication Stressmentioning
confidence: 91%
See 2 more Smart Citations
“…The authors report an increased speed of DNA replication but an unaltered number of active origins. The increase in DNA replication speed resulted in the formation of DSBs which triggered a DNA damage response in the second cell cycle after E2F6 siRNA, suggesting a different mechanism than the one reported for DNA replication stress ensuing from cyclin E overexpression (Pennycook et al, 2020 ). Interestingly, loss of E2F1 and E2F2 in mice resulted in DNA damage (Iglesias-Ara et al, 2015 ).…”
Section: E2f1 Dysregulation As a Cause Of Dna Replication Stressmentioning
confidence: 91%
“…Similarly to studies of cyclin E hyper-activity, models of hyper-activity of its upstream transcriptional activator E2F1 also show resultant DNA damage. An important example is a model of E2F hyper-activation promoted by the loss of the E2F repressor E2F6 (Pennycook et al, 2020 ). In this model, the authors used siRNA against E2F6 to study the consequences of E2F activation in S phase.…”
Section: E2f1 Dysregulation As a Cause Of Dna Replication Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The most critical genes included six up-regulated shared genes (IL6, TNF, HOXA5, POU2F2, ITGB3, and STAT1) and 12 down-regulated shared genes (YY1, E2F6, ESR1, FOXO3, FOXO1, MEF2A, ATF3, ATF4, DDIT3, TCF4, BCL2L2, and BMP4). Several other studies have previously reported the mentioned critical genes to be involved in neural proliferation and differentiation (neurodevelopment), neurotransmission, synaptic plasticity, and myelination (Each molecule is separately described and referred to in Table 9) (Yang, Lindholm et al 2002, Nakanishi, Niidome et al 2007, Ragel, Couldwell et al 2007, He and Casaccia-Bonne l 2008, Imamura, Satoh et al 2008, Lange, Chavez et al 2008, Islam, Gong et al 2009 Raivich et al 2012, Pozo, Cingolani et al 2012, Cosker, Pazyra-Murphy et al 2013, Wang, Choi et al 2013, Ma, Tang et al 2014, Mazalouskas, Jessen et al 2015, Varney, Polston et al 2015, Doan, Kinyua et al 2016, Kennedy, Rahn et al 2016, Chen, Gao et al 2017, Lizen, Moens et al 2017, Higashi, Tanaka et al 2018, Li, Jin et al 2018, Liu, Amar et al 2018, Zhu, Carmichael et al 2018, Liu, Yu et al 2019, Majidi, Reddy et al 2019, Masgutova, Harris et al 2019, Wu and Donohoe 2019, Hartman and Czyz 2020, Pennycook, Vesela et al 2020. Below, we have hypothesized how some of these in-silico identi ed critical genes can play roles in neural manifestations of COVID-19 pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In our recently published work, 5 where we explore this concept, we propose a replication capacity model, whereby cells have an intrinsic mechanism to limit the amount of DNA they can synthetize at any given time throughout S phase. We argue that a mechanism that limits the amount of DNA synthesis ensures timely completion of genome duplication independently of fluctuations in the number of active replication forks.…”
Section: Replication Capacity Determines the Length Of S Phasementioning
confidence: 99%